The Impact Of CSR, Institutional Ownership, Tax Avoidance, And Leverage On Firm Value That Moderated By Profitability - Juliana, Vina; Murni, Yetty; Astuti, Shinta Budi (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
This study aims to identify the impact of influence CSR, Institutional Ownership, Tax Avoidance, Leverage and Profitability on Firm Value as well as Profitability to be moderated variable. This study used annual report and financial statement from website IDX and each firm that use in this study. Total sample of this study is 60 that consist of 12 firm property, real estate, and building construction listing on IDX 2017 until 2021. This study used regression data panel and Moderated Regression Analysis (MRA). The results indicated that Institutional Ownership, Leverage, and Profitability has impact on firm value meanwhile CSR and Tax Avoidance does not has impact on firm value. In moderating, Profitability can increase the effect of Institutional Ownership on Firm Value and can reduce the effect of Tax Avoidance and Leverage on Firm Value. However, Profitability cannot moderate CSR on Company Value. In this study there is still a research gap. The limitations of this study only use samples of property, real estate and building construction.